ASSOCIATION OF SLEEP DEPRIVATION AND NECK PAIN AMONG INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA (IIUM) CLINICAL YEAR STUDENTS - MOHD NASIR, WAHIDA AMILIN BINTI; MOHAMAD, MOHD YUSOF (International Journal of Allied Health Sciences, 2020)
Background: Sleep deprivation disrupts the quality of life. Neck pain is attributed to sleep deprivation as reported in previous literatures. Clinical students are prone to have sleep deprivation and neck pain due to long study hours. This study aimed to determine the prevalence of sleep deprivation, neck pain and its association among undergraduate students during the clinical years. Methods: Cross-section study was performed by selecting 152 students from International Islamic University Malaysia (IIUM) participated in this study. In this study, the Pittsburgh Sleep Quality Index (PSQI), and Nordic questionnaires were used to survey the prevalence of sleep deprivation and neck pain. Results: 63.8% of the respondents suffered from sleep deprivation for the past month. The prevalence of neck pain among students during the clinical year was 36.2% for the past week and 50.7% for the past 12 months. Despite the high prevalence of sleep deprivation and neck pain, there is no significant association between sleep deprivation and neck pain both for the past week, X2(1, N=152) = 0.149, p> 0.05 and for the past 12 months, X2(1, N=152) = 2.694, p> 0.05. Conclusion: The prevalence of sleep deprivation and neck pain among IIUM Kuantan were determined despite no significant association between them.